DETERMINATION OF TOXIC METALS IN SOME AREA PLANT FOOD VALLEY ILO - Bravo A, Marta (2004)
lt has been determined the some vegetable from llo valley contains lead, cadmium and cooper. Key Words: Metllurgic plants, lead, cadmium, cooper.